Seepage effects on settling velocity - Low, Stephanie Shui Yin (2017)
In research relating to sedimentology, marine or relatable industrial processes, a particle’s terminal velocity has been a key variable to analyse when studying its settling behaviour. Terminal velocity, which is also known as the settling velocity, is defined as the constant velocity achieved when the forces acting on a free falling object reaches equilibrium. The settling velocity is studied to analyse the behaviour of particles during sedimentation, suspension and sediment transportation. However, very little or no study has concerned the settling velocity of particles in the presence of an upward seepage. An upward seepage, also known as an injection, travels in the opposite direction of gravity. Hence, the objective of this report is to investigate how an injection affects the settling velocity of a spherical particle.